Tokoh-tokoh pembaruan pendidikan Islam di Indonesia - Nata, Abuddin (Jakarta : RajaGrafindo Persada, 2005)
Biographical sketches of Muslim educators in Indonesia
Daftar pustaka : p. 433-444
Keywords: Muslim educators -- Indonesia -- Biography; Islamic education -- Indonesia